Responding second wave of COVID-19: Experience in resource limited setting of Eastern Nepal - Dangal, Binod; Ghimire, Bashudev; Gautam, Devendra; Dangal, Rajkumar; Poudel, Arjun (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Along with the surge of second wave, the recent global pandemic COVID-19 is increasingly alarming. Although the initial increase of cases was gradual, a recent drastic surge in the number of cases reflects the speed of transmission from person to person. Because of the uncontrollable increase in COVID-19 cases, a prompt and effective response to an apparently unknown overwhelming pandemic is very challenging and dubious. Dolakha, situated in eastern part of Nepal, has struggled to manage COVID-19 care with coordination, cooperation and significant response with limited resources. In this study, we have shared our experience at resource limited setting with minimum. resources regarding preparedness, responses and challenges in the management of COVID positive cases.